Reduced HDAC2 in skeletal muscle of COPD patients - To,M; Swallow,EB; Akashi,K; Haruki,K; Natanek,SA; Polkey,MI; Ito,K; Barnes,PJ (Respiratory Research, 2017)
BACKGROUND: Skeletal muscle weakness in chronic obstructive pulmonary disease (COPD) is an important predictor of poor prognosis, but the molecular mechanisms of muscle weakness in COPD have not been fully elucidated. The aim of this study was to investigate the role of histone deacetylases(HDAC) in skeletal muscle weakness in COPD. METHODS AND RESULTS: Twelve COPD patients, 8 smokers without COPD (SM) and 4 healthy non-smokers (NS) were recruited to the study. HDAC2 protein expression in quadriceps muscle biopsies of COPD patients (HDAC2/β-actin: 0.59 ± 0.34) was significantly lower than that in SM (1.9 ± 1.1, p = 0.0007) and NS (1.2 ± 0.7, p = 0.029). HDAC2 protein in skeletal muscle was significantly correlated with forced expiratory volume in 1 s % predicted (FEV1 % pred) (rs = 0.53, p = 0.008) and quadriceps maximum voluntary contraction force (MVC) (rs = 0.42, p = 0.029). HDAC5 protein in muscle biopsies of COPD patients (HDAC5/β-actin: 0.44 ± 0.26) was also significantly lower than that in SM (1.29 ± 0.39, p = 0.0001) and NS (0.98 ± 0.43, p = 0.020). HDAC5 protein in muscle was significantly correlated with FEV1 % pred (rs = 0.64, p = 0.0007) but not with MVC (rs = 0.30, p = 0.180). Nuclear factor-kappa B (NF-κB) DNA binding activity in muscle biopsies of COPD patients (10.1 ± 7.4) was significantly higher than that in SM (3.9 ± 7.3, p = 0.020) and NS (1.0 ± 1.2, p = 0.004and significantly correlated with HDAC2 decrease (rs = -0.59, p = 0.003) and HDAC5 (rs = 0.050, p = 0.012). HDAC2 knockdown by RNA interfe